KESADARAN HUKUM MASYARAKAT TERHADAP PEMBERIAN NAFKAH TIDAK HALAL DARI HASIL GAME JUDI ONLINE PERSPEKTIF IMAM SYAFI’I STUDI KASUS KELURAHAN BERNGAM KOTA BINJAI - Nuraeningsih , Evi; Nur Iqbal, Muhammad (JOURNAL EQUITABLE, 2025)
This study aims to examine the public's legal awareness regarding unlawful sustenance from online gambling games and the views of the Shafi'i school of thought on this matter. The method used is qualitative research with an empirical normative approach, which focuses on analyzing legal regulations and related legal concepts. The approach applied is a conceptual approach, which emphasizes problem-solving analysis through an understanding of legal concepts and values in the formulation of regulations. The research findings show that the public's legal awareness of unlawful sustenance from online gambling varies. Some understand it, but the environment, which treats gambling as common, leads them to continue the activity, especially under economic pressure. Others are less aware of what is lawful or unlawful, yet they are tempted by the immediate gains from online gambling without realizing that the sustenance provided to their families is unlawful. Imam Shafi'i emphasizes that sustenance from wealth obtained through unlawful means, such as usury, theft, robbery, fraud, and gambling, is not permissible for providing sustenance to oneself, family, or others. This can have negative consequences for both the giver and the receiver of the sustenance. Keywords: Legal Awareness, Unlawful Sustenance, Imam Shafi’i’s Perspective